Strategy of Thai team about trade and investment between Thai and Laos readiness for AEC : A case study of Thai Trade Center, Vientiane Office of Commercial Affairs, Royal Thai Embassy - เลิศประกายแสง, ณิชาภา (Community and Social Development Journal, 2017)
The research is aimed to study strategic planning of Thai team or Thai Trade Center in Vientiane, Laos on trade and investment in order to prepare driving of economic cooperation between Thailand and Lao People’s Democratic Republic (Lao PDR) under AEC regulations to see which direction Thailand and Lao PDR are tending to expand trade and investment in order to make stability and security under framework of bilateral relationship, and analyze if trade and investment opportunity of Thailand in Lao PDR is developed in positive way after Laos government has turned to take an interest in liberalization of trade and investment more. Research Methodology is to collect two kinds of data : collection of primary data via interview on related persons of both Thai government and private sectors in Lao PDR, and collection of secondary data via study on related papers. The study result revealed that, in Thai’s view, Laos was just not an ASEAN member but also played a key role in giving cooperation to develop ASEAN together. Therefore, the main strategy to which Thai team gave precedence is to take pulse of Laos. This means trying to adjust itself to approach to and understand Laos. With similarity on culture, language, etc., so cooperation between Thailand and Lao PDR had to be carried out carefully with respect to each other more than that to other countries in order to strengthen their relationship and business partnership. For this reason, the relationship on trade and investment between Thailand and Lao PDR was carried out in win-win situation to integrate economic cooperation stably and prepare them before entering into ASEAN Economic Community in 2016.